2017
DOI: 10.18632/oncotarget.17063
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of exportin-1 function results in rapid cell cycle-associated DNA damage in cancer cells

Abstract: Selective inhibitors of nuclear export (SINE) are small molecules in development as anti-cancer agents. The first-in-class SINE, selinexor, is in clinical trials for blood and solid cancers. Selinexor forms a covalent bond with exportin-1 at cysteine-528, and blocks its ability to export cargos. Previous work has shown strong cell cycle effects and drug-induced cell death across many different cancer-derived cell lines. Here, we report strong cell cycle-associated DNA double-stranded break formation upon the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Overcomes resistance to platinum compounds [166] In vitro Synergizes with DNA-damaging agents [187] Pediatric cancer (solid and hematological)…”
Section: In Vitromentioning
confidence: 99%
“…Overcomes resistance to platinum compounds [166] In vitro Synergizes with DNA-damaging agents [187] Pediatric cancer (solid and hematological)…”
Section: In Vitromentioning
confidence: 99%
“…In vitro studies have demonstrated cell cycle arrest, accumulation of DNA damage, and induction of apoptosis in response to treatment with SINE compounds as a result of the nuclear accumulation and reactivation of TSPs and reduced oncoproteins. 1,2,[13][14][15] We and others have previously shown that selinexor has anti-tumor activity in preclinical models of acute myeloid leukemia (AML), chronic lymphocytic leukemia (CLL), T-cell acute lymphoblastic leukemia, multiple myeloma, and diffuse large B-cell lymphoma (DLBCL). [2][3][4][15][16][17][18][19] In addition, selinexor is being tested as a single agent and in combination in ongoing phase 1 to 3 clinical trials for the treatment of advanced solid tumor and hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…XPO1 mediates the nuclear exit of Cyclin Dependent Kinase (CDK)-cyclins such as cyclin B1 (which regulates transition from G2 to M phase), tumor suppressor proteins including p53, p21, Rb and FOXO that regulate CDK-cyclins and the progression of the cell cycle 28 , 29 . Previous studies with SINE compounds have shown reduced cell division in cancer cells 30 . RSV subverts the progression of cell cycle at both mRNA and protein levels.…”
Section: Resultsmentioning
confidence: 92%